Wealth concentration in the United States using an expanded measure of net worth - Lindsay Jacobs; Elizabeth Llanes; Kevin Moore; Jeffrey P. Thompson; Alice M. Henriques (Federal Reserve Bank of Boston, 2021)
Defined benefit (DB) pensions and Social Security are two important resources for financing retirement in the United States. However, these illiquid, non-market forms of wealth are typically excluded from measures of net worth. To the extent that these broadly held resources substitute for savings, measures of wealth inequality that do not account for DB pensions and Social Security may be overstated. This paper develops an alternative, expanded wealth concept, augmenting precise net worth data from the Survey of Consumer Finances with estimates of DB pension and expected Social Security wealth. We use this expanded wealth concept to explore the concentration of wealth among households aged 40 to 59 and find that (1) including DB pension and Social Security results in markedly lower measures of wealth concentration and that (2) trends toward higher wealth inequality over time, while moderated, are still present.
Keywords: D14; D31; D63; G51; I31; J15; 330; wealth concentration; saving; Social Security; pensions